Dead certain : a novel - Mitzner, Adam (Seattle : Thomas & Mercer, 2017)
By day, Ella works as a buttoned-up attorney on some of the citys most grueling cases. By night, she pursues her passion for singing in the darkest clubs of Manhattan.
Keywords: Women lawyers -- Fiction; Sisters -- Fiction; Women authors -- Fiction; Missing persons -- Fiction; Secrecy -- Fiction